A clinical overview of non‐alcoholic fatty liver disease: A guide to diagnosis, the clinical features, and complications—What the non‐specialist needs to know. (14th September 2021) - Muthiah, Mark D.; Cheng Han, Ng; Sanyal, Arun J.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) has a rapidly rising prevalence worldwide and is the most common cause of liver disease in developed countries. In this article, we discuss the spectrum of disease of NAFLD with a focus on the earlier spectrum of the disease that is commonly encountered by non‐specialists, as well as the hepatic and extra‐hepatic associations of the disease. We discuss in detail the two common presentations of NAFLD, incidentally detected hepatic steatosis and asymptomatic raised liver enzymes, and provide an algorithm for management and continued to follow up for these patients. Considerations for the management of cardiovascular comorbidities in these patients are also discussed. Finally, we cover the topic of screening for NAFLD in high‐risk populations.